Mobility Support in Vehicular Named-Data Networking - Duarte, Joao M.; Braun, Torsten; Villas, Leandro A. (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2019)
In this thesis, Vehicular Named-Data Networking (VNDN) refers to the use of the Named-Data Networking communication model over Vehicular Ad-hoc Networks. With the aim of addressing the problems caused by mobility to efficiently support VNDN communications in highly mobile traffic scenarios, various contributions were proposed in the scope of this thesis. These contributions include a routing protocol, able to address VNDN problems such as broadcast storms and message redundancy, as well as solutions to enable content advertisements and for addressing the problems caused by reverse path partitioning, network partitioning, and source mobility. Finally, all the proposed solutions are integrated into a single framework called MobiVNDN. The evaluation results show that the proposed solutions are efficient and scalable, providing high VNDN application performance even in complex traffic scenarios